Stadtraum und B?urgerin : Aufstellungsorte kaiserzeitlicher Ehrenstatuen in Italien und Nordafrika. - Cristina Murer (Urban spaces (Walter de Gruyter & Co.) ;, 2017)
"This study addresses the key questions of where, when, and why statuary images were erected to honor female citizens in the imperial urban spaces of Italy and North Africa. Besides the primary archeological questions, the investigation focuses on issues of social history and urbanism. The volume includes a catalogue of all preserved honorific images of female Roman citizens from Italy and the Western provinces"--